2003
DOI: 10.1124/jpet.102.042028
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic and Ionic Factors in the Binding of Local Anesthetics to the Major Variant of Human α1-Acid Glycoprotein

Abstract: Understanding the interaction of local anesthetics (LAs) with plasma proteins is essential to understanding their systemic pharmacology and toxicology. The molecular determinants of LA binding to the major variant (F1*S) of human ␣ 1 -acid glycoprotein (AGP) were therefore investigated spectrofluorometrically using whole AGP and a novel, F1*S variant-selective probe previously developed in our laboratory. Equilibriumcompetitive displacement of this probe by LAs, observed by the recovery of AGP's fluorescence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…Moreover, the thermodynamic parameters did not show any correlation with the drug octanol/water partition coefficients or polar surface area (PSA) of the test compounds (Figure B,C and Table S1). This observation contrasts with the direct correlation between ∆ H º, ∆ S º, and ∆Gº and hydrophobicity (log P ) reported for the binding of a series of local anesthetics and phenothiazine neuroleptics and AGP (Miyoshi et al ., ; Urien et al ., ; Taheri et al ., ). However, it should be noted that these studies employed equilibrium dialysis or fluorometric binding assays to generate affinity constants from which the thermodynamic parameters were indirectly derived.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the thermodynamic parameters did not show any correlation with the drug octanol/water partition coefficients or polar surface area (PSA) of the test compounds (Figure B,C and Table S1). This observation contrasts with the direct correlation between ∆ H º, ∆ S º, and ∆Gº and hydrophobicity (log P ) reported for the binding of a series of local anesthetics and phenothiazine neuroleptics and AGP (Miyoshi et al ., ; Urien et al ., ; Taheri et al ., ). However, it should be noted that these studies employed equilibrium dialysis or fluorometric binding assays to generate affinity constants from which the thermodynamic parameters were indirectly derived.…”
Section: Resultsmentioning
confidence: 97%
“…From the above results, the number of binding sites ( n ) which were less than 1 for both R ‐ and S ‐mexiletine indicated that mexiletine may have selectively bound with hAGP variants [29] . Mifepristone and imipramine were the specific ligands of the F1‐S and A variants of hAGP, respectively [30,31] . In this competition binding study we investigated the binding of mexiletine enantiomers with different genetic variants of hAGP and determined the possible enantioselectivity (as shown in Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several techniques have been used to study the interactions and affinities of drugs with either HSA or AGP 5–15. These methods include ultrafiltration 5, 9, equilibrium dialysis 6, 8, fluorescence assays 7, 12, capillary electrophoresis 10, UV–Vis spectroscopy 11, and solid‐phase microextraction 13–15. Another technique used to study drug–protein interactions is high‐performance affinity chromatography (HPAC) 1, 16.…”
Section: Introductionmentioning
confidence: 99%